Experimental observation of a current-driven instability in a neutral electron-positron beam - Warwick,J; Dzelzainis,T; Dieckmann,ME; Schumaker,W; Doria,D; Romagnani,L; Poder,K; Cole,JM; Alejo,A; Yeung,M; Krushelnick,K; Mangles,SPD; et al. (Physical Review Letters, 2017)
We report on the first experimental observation of a current-driven instability developing in a quasineutral matter-antimatter beam. Strong magnetic fields (≥1  T) are measured, via means of a proton radiography technique, after the propagation of a neutral electron-positron beam through a background electron-ion plasma. The experimentally determined equipartition parameter of εB≈10−3 is typical of values inferred from models of astrophysical gamma-ray bursts, in which the relativistic flows are also expected to be pair dominated. The data, supported by particle-in-cell simulations and simple analytical estimates, indicate that these magnetic fields persist in the background plasma for thousands of inverse plasma frequencies. The existence of such long-lived magnetic fields can be related to analog astrophysical systems, such as those prevalent in lepton-dominated jets.